2007
DOI: 10.1007/s00467-007-0656-2
|View full text |Cite
|
Sign up to set email alerts
|

Dimercaptosuccinic acid (DMSA) renal scan in the evaluation of hypertension in children

Abstract: Renal scarring is known to be associated with hypertension. The primary objective of this study was to investigate the prevalence of renal scarring in children referred to our clinic with hypertension. The secondary objective was to compare renal ultrasound (US) examination with dimercaptosuccinic acid (DMSA) renal scan in diagnosing renal scars in these patients. The study included 159 patients who underwent DMSA renal scan as well as renal US for the evaluation of hypertension of unknown etiology. Thirty-thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 20 publications
0
18
2
Order By: Relevance
“…Indeed, some clinical characteristics might help in diagnosing the etiology of hypertension, but they were not fully conclusive. On the other hand, it is very important to distinguish primary and secondary hypertension for avoiding extensive investigation of the etiology of hypertension in children with primary hypertension, but without missing the detection of secondary hypertension [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some clinical characteristics might help in diagnosing the etiology of hypertension, but they were not fully conclusive. On the other hand, it is very important to distinguish primary and secondary hypertension for avoiding extensive investigation of the etiology of hypertension in children with primary hypertension, but without missing the detection of secondary hypertension [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, 21% of the children with newly diagnosed hypertension had hypertension etiology showing renal scarring (12) . During 27 years of follow-up, Jacobson concluded that the incidence of HT was 23% in cases with pyelonephritic scars secondary to reflux nephropathy (13) .…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study showed the rate of renal parenchymal scars after fi rst episode of acute pyelonephritis to be about 42% (1). The prevalence of renal scars in hypertensive children is 21% (2). Longitudinal studies estimate 3% to 30% increment of the occurrence of hypertension after longtime follow up of patients with a history of parenchymal scarring secondary to vesicoureteral refl ux (VUR) and UTI during childhood (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%